Literature Review: Pengaruh Diskon dan Promosi terhadap Keputusan Pembelian dan Permintaan Konsumen - Maharani, Hani Puspita; Aulia, Jessyka; Matondang, Khairani Alawiyah; Simamora, Leoni Geraldin Br (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of knowledge and technology continues to progress, impacting the diversity of products and changes in consumer lifestyles. As a result, companies must implement effective strategies to attract consumer purchasing interest in a competitive business environment. This study aims to identify and explain the influence of promotions and discounts on consumers' purchasing decisions and their demand for goods or services. The research method employed is a literature review using the Research Rabbit platform. The findings indicate a positive and significant relationship between discounts, promotions, and consumer purchasing decisions and demand. Furthermore, the combination of discounts and promotions proves to be more effective in increasing consumer demand.